New Islamic Schools Tradition, Modernity, and Class in Urban Pakistan - Riaz, Sanaa; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
The first ethnographic study of the trend toward religious, parochial schooling in urban Pakistan, this book provides data from over fifty-Karachi area schools to establish the complex reasons middle- and upper-class families enroll in religious Islamic schools.
Keywords: Religion; School management and organization; Education and sociology; Sociology, Urban; International and Comparative Education; Administration, Organization and Leadership